Constraint on the spectral index from primordial black holes - Yana Galarza, J. (2013)
We analyse the process of gravitational collapse using Press-Schechter theory in order to predict the existence of Primordial Black Holes, PBHs, using the Josan’s restriction and the latest cosmological parameters measured by Planck satellite. Assuming a gaussian fluctuation on the perturbation in the early Universe, we find that PBHs with mass M > 1012 kg, have not evaporated yet. Comparing with the mass fraction PBH = 10−20 and assuming that the PBHs energy density should not exceed the Cold Dark Matter, CDM, energy density, we constraint the spectral index (blue espectra) to ns < 1.4 and obtain a value of the power spectrum P ≈ 10−2.